The Effect of Disclosure of Corporate Social Responsibility and Profitability on Tax Avoidance - Bariroh, Nur; Andini, Isnani Yuli (Formosa Journal of Sustainable Research, 2024)
Tax Avoidance is a method or strategy used to minimize tax payments without breaking the law. This research was conducted on consumer sector manufacturing companies listed on the IDX in 2017-2021 using the purposive sumpling method and data was obtained from 30 sample companies. The research results show that partially CSR has a negative effect on Tax Avoidance, and profitability has a negative effect on Tax Avoidance. Simultaneously, CSR and profitability influence Tax Avoidance